Boundary Value Analysis Testing Against Library Applications Using the Black Box Method as System Performance Optimization - Gilang Ryan Fernandes; Ika Mei Lina (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2021)
The development of the use of advanced technology in the form of computerized applications has become a trend and is widely used in all fields. One of the fields that take advantage of the use of automated technology is the library. However, not all of these applications can run well by the application creation hypothesis. For this reason, application testing is required before implementation to avoid bugs or errors. Consider the application testing phase importance, testing with the black box method was carried out on library applications using the Boundary Value Analysis (BVA) technique in this study. These testing methods and techniques were chosen. When the application is implemented, there will be no more errors caused by differences in the value data during the input process with the stored value data, after testing using the black box method with the BVA technique and documentation of each test. All the library application functions have been running according to the initial application plan made, and there are no more bugs or errors when the application is run.